A Collective Biography of Twelve World-Class Leaders A Study on Developing Exemplary Leaders John R. Shoup - John R. Shoup (New York University Press of America, Inc, 2006)
This collective biography on twelve world-class leaders provides timeless principles on how families, as well as educational, civic, religious, and military organizations, can facilitate the development of exemplary leaders. The biographies and autobiographies of great leaders reveal the importance of an involved parent, happy childhood, plethora of "apprenticeships," rich formal and informal education, a steady stream of prodigious patrons, gracious critics, and a favorable fate.
Reference
Keywords: Education